Warps and waves in the stellar discs of the Auriga cosmological simulations - Gómez, Facundo A.; White, Simon D. M.; Grand, Robert J. J.; Marinacci, Federico; Springel, Volker; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society, 2017)
Recent studies have revealed an oscillating asymmetry in the vertical structure of the Milky Way's disc. Here, we analyse 16 high-resolution, fully cosmological simulations of the evolution of individual Milky Way-sized galaxies, carried out with the magnetohydrodynamic code arepo. At redshift zero, about 70 per cent of our galactic discs show strong vertical patterns, with amplitudes that can exceed 2 kpc. Half of these are typical ‘integral sign’ warps. The rest are oscillations similar to those observed in the Milky Way. Such structures are thus expected to be common. The associated mean vertical motions can be as large as 30 km s−1. Cold disc gas typically follows the vertical patterns seen in the stars. These perturbations have a variety of causes: close encounters with satellites, distant fly-bys of massive objects, accretion of misaligned cold gas from halo infall or from mergers. Tidally induced vertical patterns can be identified in both young and old stellar populations, whereas those originating from cold gas accretion are seen mainly in the younger populations. Galaxies with regular or at most weakly perturbed discs are usually, but not always, free from recent interactions with massive companions, although we have one case where an equilibrium compact disc reforms after a merger.